Circuit Training Exercises to Improve Basketball Skills - Rahmadani, Ahmad; Candra, Oki; Piranda, Muhammad Fiqih (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study includes experimental research that has been conducted in 8 training sessions. The sample in this study were students of the physical education. This study examines circuit training to improve of basketball playing skills. First, an pre test was carried out to see the level of basic basketball technique skills using instruments that had been validated by experts and trial stages on the field. After that, it entered the experimental stage. The experiment was given by implementing circuit training. The contents of the training include basic basketball technique exercises such as: dribbling, passing and shooting which are carried out in the form of posts, consisting of 5 posts. After completing the experimental stage, the researcher conducted a post test to see how far the difference was. The result was a significant increase between the comparison of the results of pre test and post test. In addition, the results of the study also provide differences in the average scores of pre test was 7.8 compared to 9.1 of the post test. The percentage increase is 65%. The t-value of 8.12 is also obtained, which is greater than the t-value in table 2.1. This means that there is a significant difference between the results of the initial test and the final test. Thus, it is proven that using circuit training can help students to improve basketball game skills.